BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PENERIMAAN IBU TERHADAP IMUNISASI MEASLES RUBELLA PADA ANAK SD DI DESA GUMPANG, KECAMATAN KARTASURA, KABUPATEN SUKOHARJO - Gayuh Mustika Prabandari; Syamsulhuda BM; Aditya Kusumawati (Jurnal Kesehatan Masyarakat (Undip), 2018)
Measles-Rubella immunization campaign is a government strategy to achieve elimination of measles and rubella by 2020. This imunization is targeting all Indonesian children between the ages of nine months and 15 years and will aim to reach 95% immunisation coverage. The fact is that not all parents receive this immunization program. Gumpang village is one of the villages with high immunization rejection.Thisstudy isaimed toanalyzethe factorsassociatedwith mother’s acception of measles-rubella imunization at Gumpang, Sukoharjo.This research is a quantitative study with descriptive-analytics method. This research uses  simple random sampling techniques  and  the  data  are  collected  using questionnaire with interview method. Data analysis procedure of this research uses univariate and bivariate with chi-square test.The result shows that 27,7% respondents did not receive measles-rubella immunization. The result of chi-square test shows that knowledge abaout measles-rubella imunization (p= 0,006), perceived severity (p= 0,012), perceived benefit (p= 0,004) and perceived barriers (0,000) are significantly associated with the acceptance of measles-rubella imunization. While age variable (p=1,288), job status (p= 0,702), education level (p= 0,533), perceived susceptibility  (p=  0,145), family support (p=  0,464) and environmental support (p= 0,408) are  not  significantly associated with the acceptance of measles-rubella imunization.Suggestion from this research is the need to give more education about the importance of measles-rubella imunization from related parties to the parents, especially for mother, to improve their awareness to join measles and rubella imunization.